Reading tea leaves worldwide: Decoupled drivers of initial litter decomposition mass‐loss rate and stabilization - Judith M. Sarneel; Mariet M. Hefting; Taru Sandén; Johan van den Hoogen; Devin Routh; Bhupendra S. Adhikari; Juha M. Alatalo; Alla Aleksanyan; Inge H. J. Althuizen; Mohammed H. S. A. Alsafran; Jeff W. Atkins; Laurent Augusto; et al. (Ecology Letters, 2024)
The breakdown of plant material fuels soil functioning and biodiversity. Currently, process understanding of global decomposition patterns and the drivers of such patterns are hampered by the lack of coherent large‐scale datasets. We buried 36,000 individual litterbags (tea bags) worldwide and found an overall negative correlation between initial mass‐loss rates and stabilization factors of plant‐derived carbon, using the Tea Bag Index (TBI). The stabilization factor quantifies the degree to which easy‐to‐degrade components accumulate during early‐stage decomposition (e.g. by environmental limitations). However, agriculture and an interaction between moisture and temperature led to a decoupling between initial mass‐loss rates and stabilization, notably in colder locations. Using TBI improved mass‐loss estimates of natural litter compared to models that ignored stabilization. Ignoring the transformation of dead plant material to more recalcitrant substances during early‐stage decomposition, and the environmental control of this transformation, could overestimate carbon losses during early decomposition in carbon cycle models.

Regulation of nitrogen fixation from free-living organisms in soil and leaf litter of two tropical forests of the Guiana shield - Leandro Van Langenhove; Thomas Depaepe; Sara Vicca; Joke van den Berge; Clement Stahl; Elodie Courtois; James Weedon; Ifigenia Urbina; Oriol Grau; Dolores Asensio; Josep Peñuelas; Pascal Boeckx; et al. (Plant and Soil, 2020)

CaaX-prenyltransferases are essential for expression of genes involvedin the early stages of monoterpenoid biosynthetic pathwayin Catharanthus roseus cells - Vincent Courdavault; Martine Thiersault; Martine Courtois; Pascal Gantet; Audrey Oudin; Pierre Doireau; Benoit St-Pierre; Nathalie Giglioli-Guivarc’h (Plant Molecular Biology, 2005)

Quantification of bacterial subgroups in soil: comparison of DNA extracted directly from soil or from cells previously released by density gradient centrifugation - Sophie Courtois; Åsa Frostegård; Pernilla Göransson; Geraldine Depret; Pascale Jeannin; Pascal Simonet (Environmental Microbiology, 2001)
All molecular analyses of soil bacterial diversity are based on the extraction of a representative fraction of cellular DNA. Methods of DNA extraction for this purpose are divided into two categories: those in which cells are lysed within the soil (direct extraction) and those in which cells are first removed from soil (cell extraction) and then lysed. The purpose of this study was to compare a method of direct extraction with a method in which cells were first separated from the soil matrix by Nycodenz gradient centrifugation in order to evaluate the effect of these different approaches on the analysis of the spectrum of diversity in a microbial community. We used a method based on polymerase chain reaction (PCR) amplification of a 16S rRNA gene fragment, followed by hybridization of the amplified fragments to a set of specific probes to assess the phylogenetic diversity of our samples. Control parameters, such as the relationship between amount of DNA template and amount of PCR product and the influence of competing DNA on PCR amplification, were first examined. Comparison between extraction methods showed that less DNA was extracted when cells were first separated from the soil matrix (0.4 µg g −1 dry weight soil versus 38–93 µg g −1 obtained by in situ lysis methods). However, with the exception of the γ‐subclass of Proteobacteria, there was no significant difference in the spectrum of diversity resulting from the two extraction strategies.